Concomitant Presence of Allergic Rhinitis (AR) in Chronic/Fibrotic Hypersensitivity Pneumonitis (C/F-Hp) Patients: Coincidence or Correlation - Ayyaz, Salman; Shakeel Ahmad Khan; Mudassar Rasool; Sumbal Ayyaz; Muhammad Atif (Annals of King Edward Medical University, 2025)
Background: Chronic/Fibrotic Hypersensitivity Pneumonitis (C/F-HP), inspite of its high prevalence, is often underdiagnosed due to the complexity of its diagnostic process, which typically involves lung biopsies. These invasive procedures carry significant risks, especially for patients who are severely ill. This study explores the potential of Allergic Rhinitis as a non-invasive clinical indicator for diagnosing C/F-HP, aiming to simplify the diagnostic approach and reduce the need for biopsies. Objective: To assess the occurrence of AR in patients with C/F-HP and evaluate its utility as a clinical marker for non-invasive diagnosis. Method: This cross-sectional descriptive study was conducted at BAM&DC between July 2021 and December 2022. A total of 107 patients diagnosed with C/F-HP, aged 18 to 60, were enrolled using a consecutive sampling technique. The exclusion criteria included patients with known causes of Interstitial Lung Disease and comorbid conditions. Allergic Rhinitis was diagnosed based on clinical history and serum IgE levels, following AAFP guidelines. Results: The study comprised 107 C/F-HP patients, with a mean age of 46.73 ± 9.36 years. Male patients accounted for 59.8% of the cohort. AR was diagnosed in 99 out of 107 patients (92.5%), with an average serum IgE level of 542.65 ± 182.93. A small percentage (3.7%) of AR patients had normal IgE levels, possibly due to prior corticosteroid use. Among AR-positive patients, males outnumbered females (62:37), reflecting a similar ratio in the overall C/F-HP population. Conclusion: This study highlights a significant correlation between AR and C/F-HP, suggesting that AR could serve as a reliable clinical indicator for C/F-HP diagnosis, potentially reducing the need for invasive lung biopsies. It seems that our Hypothesis “in an uncertain ILD patient, if AR is concomitantly present, C/F-HP should be sought out”, stands validated. Further research is recommended to solidify these findings.